Growth Pattern and Condition Factors Euthynnus affinis (Cantor, 1849) Landed at Lempasing Fishing Port, Bandar Lampung - Putriani, Rizha Bery; Reza, Muhammad; Julian, David; Eka Putri, Septi Malidda (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
This research was conducted at PPP Lempasing between March until May 2024 to explore the growth patterns and condition factors of the little tuna (Euthynnus affinis). The results indicate that the growth pattern of this species is negatively allometric, with a coefficient (b) value of 2.7178. The average condition factor of the fish ranges from 0.428 to 1.187, suggesting a slim body shape and that the fish are not overly fat. This negative allometric growth pattern means that the length of the fish grows faster than its weight, which may indicate stress or environmental challenges. The low condition factor suggests that the fish are not in optimal condition, possibly due to a lack of food or unfavorable environmental factors. Additionally, the frequency distribution of the little tuna lengths shows that the sizes caught range from 230 to 520 mm, with the highest frequency in the size class of 370-389 mm and the lowest in the 510-529 mm class. It is necessary to implement medium-term management strategies such as improving human resource quality, empowering fishing communities through alternative livelihoods, and developing environmentally friendly fishing gear.